The impact of epithelial-mesenchymal transition (EMT) induced by metabolic processes and intracellular signaling pathways on chemo-resistance, metastasis, and recurrence in solid tumors - Mahsa Liaghat; Saeid Ferdousmakan; Seyedeh Haniyeh Mortazavi; Sheida Yahyazadeh; Asrin Irani; Sara Banihashemi; Fatemeh Sadat Seyedi Asl; Abdullatif Akbari; Farnoosh Farzam; Fatemeh Aziziyan; Maryam Bakhtiyari; Mohammad Javad Arghavani; et al. (Cell Communication and Signaling)
Abstract The intricate cellular process, known as the epithelial-mesenchymal transition (EMT), significantly influences solid tumors development. Changes in cell shape, metabolism, and gene expression linked to EMT facilitate tumor cell invasion, metastasis, drug resistance, and recurrence. So, a better understanding of the intricate processes underlying EMT and its role in tumor growth may lead to the development of novel therapeutic approaches for the treatment of solid tumors. This review article focuses on the signals that promote EMT and metabolism, the intracellular signaling pathways leading to EMT, and the network of interactions between EMT and cancer cell metabolism. Furthermore, the functions of EMT in treatment resistance, recurrence, and metastasis of solid cancers are covered. Lastly, treatment approaches that focus on intracellular signaling networks and metabolic alterations brought on by EMT will be discussed.